Fenomena Penggunaan Bahasa Gaul di Kalangan Mahasiswa PBSI Semester 3 - Katharina Woli Namang; Nuraini Ma'u (Jurnal Pustaka Cendekia Pendidikan, 2025)
Slang is a dialect of the non-formal Indonesia language used By the community. Students are teenagers who often use slang, this causes students to have difficulty speaking formal language and directlyp influences the haracter of the Indonesian language. Knowing the extent to which slang influences Indonesian omong people PBSI students. To describe the results of the questionnaire and determine the impact of slang on students. This research uses quantitative descripyive methods. Data collection techniques include questionnaire and direct observation. The respodents were 9PBSI students at Muhammadyah Universirty, Maumere. Slang is commonly used by students. Slang has been used as everyday language. The use of slang is rarely used in the campus environment. Slang will have a bad influence on the of Indonesian because use takes a long time to eliminate it. However, Slang is difficult to eliminate among teenagers. For this reason, we will further develop the influences that the use of slang among teenagers.